The Implementation of Mind Mapping in Arabic Speaking skills for University Students - Ida Miftakhul Jannah; Umi Hanifah; Mohamad Thohir (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2023)
This study aims to describe the implementation of mind mapping in the learning process of Arabic speaking skills. This research is qualitative research conducted at the Arabic Language Departement (PBA) at UIN Sunan Ampel Surabaya with a purposive sample of second-semester student. The results of this study showed, that the process of learning Arabic speaking skills using mind mapping in PBA Sunan Ampel is carried out in two stages. The first stage is making a mind map based on the theme that they have listened. In the second stage, after the students have finished making the main idea in the form of the mind mapping, the students practice Arabic speaking based on themes listened and what has been written in mind mapping. The students were able to describe and present themes verbally properly, completely, and coherently with the help of mind mapping. This mind mapping is in the form of mind ideas which are written in curved lines, colorful, and using symbols coherently starting from the first idea to the end of the theme. With this mind mapping, students can easily tell the theme. But there are a few obstacles experienced by students whose vocabulary is still limited. The solution for students who still lack mastery of their vocabulary is by writing important vocabularies related to the theme being studied in each main idea written in the mind mapping. This way is well in helping them to describe and present the theme.